Analysis of the reduction of trans-fatty-acid levels in the foods of Argentina. (17th November 2018) - Kakisu, Emiliano; Tomchinsky, Eliana; Victoria Lipps, María; Fuentes, Juan
Abstract: Adverse health effects found to be caused by the industrial trans fatty acids (TFAs) encouraged significant changes in the food supply. A working model was implemented based on a multisectoral approach to monitor progress in the reduction of TFAs in compliance with Argentine food regulations. We analysed the fatty-acid profiles of commercial foods over the entire country comparing the results before and after the deadline for the compliance. A 93% adherence in the foods was obtained after the finalisation of the deadline for the compliance with the limited use of partially hydrogenated vegetable oils. The analytical monitoring was a key tool operating for the compliance by the food manufacturers. The industrial TFAs were mostly replaced by semisolid fractions of vegetable oils containing high percentages of saturated fatty acids. Promising innovations for the food industry were established that provided more healthful alternative substitutes for TFAs.